2023
DOI: 10.1371/journal.pone.0281604
|View full text |Cite
|
Sign up to set email alerts
|

Two is better than one: Apologies from two robots are preferred

Abstract: Although the capabilities of service robots are increasing, avoiding any mistakes is difficult. Therefore, strategies for mitigating mistakes, such as apology behavior designs, are essential for service robots. Past studies reported that costly apology is perceived as more sincere than non-costly ones and more acceptable. To increase the apology cost in robot service situations, we thought that using multiple robots would increase the perceived costs in the of financial, physical, and time costs. Therefore, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Previous studies have mainly focused on enhancing social presence through their appearance and functions of agents (Liu et al, 2022;Lohse et al, 2008;MacDorman & Ishiguro, 2006;Song & Luximon, 2020;Straub, 2016;Takahashi et al, 2022). There were also several studies showing that communication between multiple agents and humans attracts more human attention than communication between single agents and humans, because highlighting the social connections between agents improves human imagination towards the agents (Iio et al, 2017;Okada et al, 2023;Yoshikawa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have mainly focused on enhancing social presence through their appearance and functions of agents (Liu et al, 2022;Lohse et al, 2008;MacDorman & Ishiguro, 2006;Song & Luximon, 2020;Straub, 2016;Takahashi et al, 2022). There were also several studies showing that communication between multiple agents and humans attracts more human attention than communication between single agents and humans, because highlighting the social connections between agents improves human imagination towards the agents (Iio et al, 2017;Okada et al, 2023;Yoshikawa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We expected that presenting a social background to the stuffed animal's owner would increase the social presence of the stuffed animal to the owner. Previous studies have shown that the social presence of a robot improved when multiple robots were present, compared to when a single robot was present (Iio et al, 2017;Okada et al, 2023;Yoshikawa et al, 2017). However, to our knowledge, no study has examined whether presenting owners with a scene of an agent's computer generated (CG) avatar interacting with other agent avatars in a virtual space improves the agent's social presence.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicate that coordinated interaction between multiple robots can motivate conversations, even when speech recognition faces challenges [16], [17]. Other research highlights the enhancement of emotional aspects, such as cuteness [18] or apology [19], through the use of multiple robots. Conversely, for the operator, a study suggests that using multiple robots can improve telepresence [20].…”
Section: Related Workmentioning
confidence: 99%